Combined exposure to three heavy metals and the risk of age-related macular degeneration in the Korean population - Soonsu Shin; Jae-Hong Ryoo (Scientific Reports)
Abstract Toxicological and histological evidence suggests that heavy metals accumulate in the retina, implicating their potential role in the development of age-related macular degeneration (AMD). However, most prior epidemiologic studies have focused on individual metal exposures, overlooking possible joint effects. This study assessed the association between co-exposure to lead (Pb), mercury (Hg), and cadmium (Cd) and AMD risk among Korean adults using 2008–2012 Korea National Health and Nutrition Examination Survey data. A total of 4818 participants aged 40 years or older were included. Logistic regression models evaluated single-metal associations, while quantile g-computation and Bayesian kernel machine regression (BKMR) assessed mixture effects. Participants in the third quartile of Pb had significantly higher odds of AMD (adjusted OR: 1.76, 95% CI: 1.07–2.88) than those in the lowest quartile. Quantile g-computation showed that a one-quartile increase in the metal mixture was associated with elevated AMD risk (adjusted OR: 1.20, 95% CI: 1.02–1.41). BKMR confirmed that the heavy metal mixture increased the risk of AMD, with Pb being the primary contributor in smokers and Cd in non-smokers. Our findings indicate that co-exposure to heavy metals elevates AMD risk and that the predominant contributing metal may differ depending on smoking status.